PROSES KOREOGRAFI TARI MARANDANG DI SANGGAR LINDANG UREK KOTA PAYAKUMBUH - Fauzhandra, Zacky; Asriati, Afifah (Universitas Negeri Padang, 2025)
This study aims to explain and analyse the choreography process of Marandang Dance at Sanggar Lindang Urek in Payakumbuh City. This type of research is qualitative with a descriptive method. The main instrument in this research is the researcher themselves, assisted by writing tools, a camera, and a voice recorder. Data were collected through literature review, observation, interviews, and documentation. The steps in analysing data are data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the choreography process of Marandang Dance at Sanggar Lindang Urek in Payakumbuh City is carried out through the management of movement, space, and time, with the choreographer successfully presenting a creative dance work that remains rooted in tradition. The compilation of all exploration and improvisation results into a complete performance. The choreographer arranges the dance structure based on the sequence of Marandang activities, considering the balance between male and female dancers, as well as the use of props such as kuali, sanduak, talam, and piriang. The movements are meaningful as each one represents a stage in the Marandang activity. Male movements are stronger and more vigorous, while female movements are more graceful yet powerful. Space is presented through diagonal, circular, and horizontal floor patterns. The dancers' body movements make extensive use of positive space with wide and deep dimensions. Time includes a medium to fast tempo, dynamic rhythms in harmony with the music, and the performance lasts approximately 7 minutes.